S113 Haemophilus influenzae stimulation of alveolar macrophages from COPD patients; effects of corticosteroids. (14th November 2013) - Khalaf, R; Lea, S; Metcalfe, H; Singh, D
Abstract : Background: The lower airways of COPD patients are often chronically colonised by bacteria such as Non-typeable Haemophilus influenza (NTHI). Bacteria are a common cause of COPD exacerbations. Corticosteroids are often used to prevent and treat COPD exacerbations. The aim of this study was to investigate the effect of corticosteroids on the in vitro inflammatory response of COPD alveolar macrophages (AM) to NTHI infection. We also investigated the cell signalling pathways activated by NTHI infection. Methods: AM from 12 COPD patients and 9 smoking controls were infected with live NTHI at multiplicity of infection (MOI) of 100:1 (bacteria: AM) for 24 hours. AM were pre-treated with dexamethasone (up to 1µM) for 1 hour. Supernatants were analysed for TNF-α, IL-6, IL-8 and IL-10 by ELISA. AM protein was extracted for Western blot analysis of nuclear factor κB (NFκB), p38 and extracellular regulated mitogen activated protein kinases (p38 and ERK) activation. Results: NTHI stimulated release of TNF-α, IL-6, IL-8 and IL-10 (p < 0.05) from both COPD patients and controls. TNF-α, IL-6 and IL-10 production was significantly inhibited by dexamethasone at 1 and 0.1µM (p < 0.05). Inhibition of TNF-α and IL-6 release was significantly higher in AM from smokers compared to COPD patients. Dexamethasone had no effect on IL-8 production (see table 1 ). NTHI infection activated NFκB, p38 and ERK MAPK signalling pathways in AM. Conclusion: NTHI infection stimulated COPD AM to release inflammatory cytokines which are only partially responsive to corticosteroids; importantly, there was no suppression of the neutrophil chemoattractant IL-8. The production of this corticosteroid resistant chemokine is associated with NF-κB and MAPK activation; these signalling pathways drive bacteria induced inflammation in COPD airways.